EPDA: Efficient and Privacy-Preserving Data Collection and Access Control Scheme for Multi-Recipient AMI Networks - Ahmad Alsharif (IEEE Access, 2019)
Advanced metering infrastructure (AMI) networks allow the data collection of consumers' fine-grained power consumption data (PCD) to perform real-time monitoring and energy management. However, PCD can leak sensitive information about consumers' activities. Various privacy-preserving data collection schemes have been proposed for AMI networks to allow the collection of an aggregated PCD to preserve consumers' privacy. However, most of these schemes are designed for single-recipient AMI networks and cannot be used efficiently for multi-recipient AMI networks in which several entities should have access to the aggregated PCD of different sets of users for legitimate uses. In this paper, we propose an efficient and privacy-preserving data collection and access control scheme for multi-recipient AMI networks named EPDA. We developed a novel proxy re-encryption scheme that allows data aggregation before re-encryption and can allow either full or partial access to the aggregated data after re-encryption as needed. The proposed scheme can be used for fine-grained access control for multi-recipient AMI networks in which each recipient can access only the data intended to it. The EPDA uses lightweight operations in encryption, aggregation, and decryption which result in low computation and communication overheads. Our security analysis demonstrates that the EPDA is secure, can resist collusion attacks and hide customers' distribution which is needed for a fair electricity trade market. Our experimental results confirm that the EPDA has improved performance for the computational cost at each entity in the AMI network and low communication overhead.